Culturing human iPSC-derived neural progenitor cells on nanowire arrays: mapping the impact of nanowire length and array pitch on proliferation, viability, and membrane deformation. Issue 47 (29th November 2021) - Harberts, Jann; Bours, Katja; Siegmund, Malte; Hedrich, Carina; Glatza, Michael; Schöler, Hans R.; Haferkamp, Undine; Pless, Ole; Zierold, Robert; Blick, Robert H.
Abstract : We tested the growth of human iPSC-derived NPCs on nanowire arrays across a wide range of array characteristics. The proliferation, viability, and interaction with the nanowire arrays were mapped depending on the array pitch and nanowire length. Abstract : Nanowire arrays used as cell culture substrates build a potent tool for advanced biological applications such as cargo delivery and biosensing. The unique topography of nanowire arrays, however, renders them a challenging growth environment for cells and explains why only basic cell lines have been employed in existing studies. Here, we present the culturing of human induced pluripotent stem cell-derived neural progenitor cells on rectangularly arranged nanowire arrays: In detail, we mapped the impact on proliferation, viability, and topography-induced membrane deformation across a multitude of array pitches (1, 3, 5, 10 μm) and nanowire lengths (1.5, 3, 5 μm). Against the intuitive expectation, a reduced proliferation was found on the arrays with the smallest array pitch of 1 μm and long NWs. Typically, cells settle in a fakir-like state on such densely-spaced nanowires and thus experience no substantial stress caused by nanowires indenting the cell membrane. However, imaging of F-actin showed a distinct reorganization of the cytoskeleton along the nanowire tips in the case of small array pitches interfering with regular proliferation. For larger pitches, the cell numbers depend on the NW lengths but proliferation generally continued although heavy deformations of the cell membrane were observed caused by the encapsulation of the nanowires. Moreover, we noticed a strong interaction of the nanowires with the nucleus in terms of squeezing and indenting. Remarkably, the cell viability is maintained at about 85% despite the massive deformation of the cells. Considering the enormous potential of human induced stem cells to study neurodegenerative diseases and the high cellular viability combined with a strong interaction with nanowire arrays, we believe that our results pave the way to apply nanowire arrays to human stem cells for future applications in stem cell research and regenerative medicine.